2015
DOI: 10.4314/rj.v2i1.4f
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS-Related Stigma and Discrimination in Workplaces in Tanzania

Abstract: Background: Stigma and discrimination against people living with and affected by HIV/AIDS undermines the effectiveness of national efforts to prevent and control the HIV epidemic. In the context of Tanzania, evidence on the incidence of HIV/AIDS-related stigma and discrimination from the perspective of the employees and employers is limited. Objective: To provide an assessment of the pervasiveness of HIV/AIDS-related stigma and discrimination in the workplace in Tanzania. Methods: A cross-sectional study, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 14 publications
3
5
0
Order By: Relevance
“…Whereas HIV testing is a crucial step in the fight against HIV/AIDS, some employees still fear testing for HIV at the workplace due to fear attached to HIV stigma and discrimination from coworkers and employers. Consistent with our findings, studies have revealed that most employees feared testing for HIV at the workplace due to fear of HIV stigma and discrimination by coworkers and by employers [16,18,46,65]. However, according to the international best practices and particularly the ILO Discrimination Convention [66], an employee has the right to privacy and confidentiality regarding his/her HIV/AIDS status and freedom from discrimination on the ground of the said status.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Whereas HIV testing is a crucial step in the fight against HIV/AIDS, some employees still fear testing for HIV at the workplace due to fear attached to HIV stigma and discrimination from coworkers and employers. Consistent with our findings, studies have revealed that most employees feared testing for HIV at the workplace due to fear of HIV stigma and discrimination by coworkers and by employers [16,18,46,65]. However, according to the international best practices and particularly the ILO Discrimination Convention [66], an employee has the right to privacy and confidentiality regarding his/her HIV/AIDS status and freedom from discrimination on the ground of the said status.…”
Section: Discussionsupporting
confidence: 85%
“…In one of the studies conducted in Australia, increased social support was associated with less HIV centrality, less internalised stigma, and less psychological distress [67]. Studies conducted among medium and large sized African workplaces demonstrated that employees will be more interested in taking up HIV testing if they know there is support available in case they are found to be HIV positive [18,68]. As a result of HIV-related stigma and discrimination, some individuals are denied necessary social support [44,69].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations